(untitled) (Swiss Medical Weekly, 2011)
Objectives: Ambrosia is spreading invasively in many European countries. Therefore, surveys showing the long-term consequences regarding the prevalence of sensitisation and allergy rates are needed. The aim of this study was to analyse the development of Ambrosia sensitisation and clinical symptoms over a period of 20 years among the patients of the allergy unit in Legnano in relation to the measured pollen concentrations. Legnano is situated near Milan in a region in northern Italy, known for its high Ambrosia pollen loads. METHODS: The sensitisation of patients to Ambrosia and other aeroallergens was tested by a skin prick test. The patients were interviewed about their clinical symptoms and the time of incidence of the symptoms. On average, 1100 patients per year were included in this study in the years 1989–2008. The daily pollen concentration was measured with volumetric Hirst type pollen traps. RESULTS: The sensitisation rate to Ambrosia increased from 24% to over 70% among the patients whose skin prick tests were positive to pollen. In 1989, about 45% of the Ambrosia sensitised patients suffered from respiratory symptoms (rhinitis and/or asthma) in late summer. After 5 years, this percentage increased to 70% and finally reached 90%. The prevalence of asthma was initially 30% among the Ambrosia sensitised patients and increased slightly to 40%. CONCLUSION: The extent of the consequences of high Ambrosia pollen concentrations is not ascertainable over the short term. Sensitisation rates have constantly increased over a period of more than 15 years, and moreover the incidence of allergy is delayed during the first years.